Innovative Learning Model Based on the Value Clarification Technique - Octia, Aniesya; Fatimah, Aulia; Adinda, Catur Putriyani Charisma; Anwar, Chairul (The Future of Education Journal, 2024)
The Value Clarification Technique (VCT) is an innovative educational strategy designed to help students internalize moral, ethical, and social values through a process of discussion, reflection, and value exploration. This approach encourages students to examine and clarify their values, fostering personal growth and a deeper understanding of moral principles. This study uses a literature review method to investigate the effectiveness of VCT, its implementation in various educational settings, and the challenges that educators face when applying this method. The findings suggest that VCT significantly improves students' critical thinking abilities, enhances their capacity for collaborative learning, and helps instill strong moral values that influence their behavior and decision-making. Furthermore, the study emphasizes that the successful implementation of VCT requires more than just the use of specific techniques; it necessitates comprehensive teacher training to equip educators with the skills to facilitate value-based discussions effectively. An inclusive and supportive learning environment is also critical, where students feel safe to express their thoughts and engage in meaningful dialogue. Additionally, VCT should be adapted to the cultural contexts and diverse backgrounds of students to ensure its relevance and effectiveness. With the right principles in place, VCT has the potential to produce individuals with not only a strong moral foundation but also the ability to think critically and act responsibly in various social contexts. This study highlights the transformative power of VCT in shaping students into well-rounded individuals who can contribute positively to society.